2012
DOI: 10.1371/journal.pone.0032916
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Species, Sexual and Individual Variations in Foraging Strategies of Fur Seals Revealed by Stable Isotopes in Whiskers

Abstract: BackgroundIndividual variations in the use of the species niche are an important component of diversity in trophic interactions. A challenge in testing consistency of individual foraging strategy is the repeated collection of information on the same individuals.Methodology/Principal FindingsThe foraging strategies of sympatric fur seals (Arctocephalus gazella and A. tropicalis) were examined using the stable isotope signature of serially sampled whiskers. Most whiskers exhibited synchronous δ13C and δ15N oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 57 publications
11
124
2
Order By: Relevance
“…Given that sea lions were only tracked across a 2-month period, we cannot make conclusions about whether these individual behavioral patterns may persist across longer temporal scales. Studies of other otariids have found that fidelity to a single foraging strategy is often retained across multiple years (Chilvers and Wilkinson 2009;Kernaléguen et al 2012;Baylis et al 2015;Kernaléguen et al 2016); however, many of these studies have focused on populations that inhabit less variable environments than the CCS. Villegas-Amtmann et al (2011) found that adult female California sea lions from the Gulf of Mexico exhibited three foraging strategies during the warm, unproductive season, but only one during the cold season, indicating that the degree of intraspecific variability in behavior may be driven by Dive rate (dives h −1 ) 19.6 ± 6.8 24.7 ± 5.6 NA 13.2 ± 2.8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that sea lions were only tracked across a 2-month period, we cannot make conclusions about whether these individual behavioral patterns may persist across longer temporal scales. Studies of other otariids have found that fidelity to a single foraging strategy is often retained across multiple years (Chilvers and Wilkinson 2009;Kernaléguen et al 2012;Baylis et al 2015;Kernaléguen et al 2016); however, many of these studies have focused on populations that inhabit less variable environments than the CCS. Villegas-Amtmann et al (2011) found that adult female California sea lions from the Gulf of Mexico exhibited three foraging strategies during the warm, unproductive season, but only one during the cold season, indicating that the degree of intraspecific variability in behavior may be driven by Dive rate (dives h −1 ) 19.6 ± 6.8 24.7 ± 5.6 NA 13.2 ± 2.8…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been increasing documentation of different foraging strategies within pinniped populations, with a particular focus on the various strategies used by individuals in the same demographic group (Cherel and Hobson 2007;Villegas-Amtmann et al 2008;Weise et al2010;Kernaléguen et al 2012;Villegas-Amtmann et al 2013). These foraging strategies often reflect the three basic diving patterns exhibited by air-breathing marine predators (epipelagic, mesopelagic, benthic), but also may be related to associations with oceanographic features, habitat use, or foraging site fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…Females from Crozet (and their corresponding whisker isotopic results) are the same individuals as those in the study by Kernaléguen et al . (). Seals breeding in Crozet were also weighed using a suspension scale (±0·1 kg).…”
Section: Methodsmentioning
confidence: 97%
“…; Kernaléguen et al . ), suggesting an adaptation of the foraging behaviour to the co‐occurrence of the competitor species. Secondly, fur seals have been intensively hunted during the 18th and 19th centuries, with commercial sealing resulting in local extinction of the two species.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrissae of otariids, such as Antarctic fur seals Arctocephalus gazella (Walters 2014), and Steller sea lions Eumetopias jubatus (Hirons et al 2001), grow linearly and are retained for multiple years (Hirons et al 2001;Cherel et al 2009;Kernaléguen et al 2012). In contrast, the vibrissae of phocids, such as grey seals Halichoerus grypus, and P. vitulina, grow asymptotically and are characterised by an asynchronous growth and replacement pattern (Greaves et al 2004;Hall-Aspland et al 2005;Beltran et al 2015).…”
Section: Introductionmentioning
confidence: 99%